Determinants of possession of the ball in soccer - Lago, C.; Martin, R. (Journal of Sports Sciences, 2006)
In research on the importance of the possession of the ball in soccer, little attention has been paid to its determinants. Using data from 170 matches of the 2003 - 2004 Spanish Soccer League, we explain why differences in the possession of the ball among teams are so great. In particular, four variables are examined: evolving match status (i.e. whether the team is winning, losing or drawing), venue (i.e. playing at home or away), and the identities of the team and the opponent in each match. Results of linear regression analysis show that these four variables are statistically significant and together explain most of the variance in possession. In short, home teams have more possession than away teams, teams have more possession when they are losing matches than when winning or drawing, and the identity of the opponent matters - the worse the opponent, the greater the possession of the ball. Combinations of these variables could be used to develop a model that predicts possession in soccer.